Selection of the Register File Size and the Resource Allocation Policy on SMT Processors - Alastruey, Jesús; Monreal, Teresa; Cazorla, Francisco; Viñals, Víctor; Valero, Mateo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2008: Anais do XX International Symposium on Computer Architecture and High Performance Computing, 2008)
The performance impact of the Physical Register File(PRF) size on Simultaneous Multithreading processors has not been extensively studied in spite of being a critical shared resource. In this paper we analyze the effect on performance of the PRF size for a broad set of resource allocation policies (Icount, Stall, Flush, Flush++, Static,Dcra and Hill-climbing) and evaluate them under two metrics: instructions per second (IPS) for throughput and harmonic mean of weighted IPCs (Hmean-wIPC) for fairness. We have found that resource allocation policy and PRF size should be considered together in order to obtain the best score in the proposed metrics. For instance, for the analyzed 2 and 4-threaded SPEC CPU2000 workloads,small PRFs are best managed by Flush, whereas for larger PRFs, Hill-climbing and Static lead to the best values for the throughput and fairness metrics, respectively.The second contribution of this work is a simple procedure that, for a given resource allocation policy, selects the PRF size that maximizes IPS and obtains for Hmean-wIPC a value close to its maximum. According to our results, Hill-climbing with a 320-entry PRF achieves the best figures for 2-threaded workloads. When executing 4-threaded workloads, Hill-Climbing with a 384-entry PRF achieves the best throughput whereas Static obtains the best throughput-fairness balance.